2018
DOI: 10.21206/rbas.v8i3.2995
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos De Adubação Nitrogenada De Cobertura Em Milho Consorciado

Abstract: O objetivo do trabalho foi avaliar o efeito do consórcio entre o milho, Brachiaria decumbens e feijão guandu (Cajanus cajan) plantados simultaneamente, sob diferentes níveis de nitrogênio em cobertura. O experimento foi realizado no ano agrícola 2011/12 na área experimental da Universidade Federal do Tocantins – UFT, localizada em Gurupi, Tocantins, Brasil. As doses de N foram 0, 40, 80, 120, 160 e 200 kg ha-1, utilizando delineamento experimental em blocos ao acaso com três repetições e 24 tratamentos. Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
0
0
1
Order By: Relevance
“…Considering the N rates, the yield of the hybrids in Sete Lagoas in 2016 and the foliar levels of N in the two locations over two years increased linearly (Figure 2). This result corroborates several studies showing the high potential of corn grain yield and N leaf contents in response to nitrogen fertilization (Peruzzo et al, 2015;Portugal et al, 2017;Scotta et al, 2018;Moreira et al, 2019). There was no effect for total fumonisins, and the two hybrids' average values were below the LMT, except at Sete Lagoas in 2016 for the N rates of 0, 80, and 240 kg ha -1 .…”
Section: Experiments With Genotypes and Nitrogen Ratessupporting
confidence: 90%
See 1 more Smart Citation
“…Considering the N rates, the yield of the hybrids in Sete Lagoas in 2016 and the foliar levels of N in the two locations over two years increased linearly (Figure 2). This result corroborates several studies showing the high potential of corn grain yield and N leaf contents in response to nitrogen fertilization (Peruzzo et al, 2015;Portugal et al, 2017;Scotta et al, 2018;Moreira et al, 2019). There was no effect for total fumonisins, and the two hybrids' average values were below the LMT, except at Sete Lagoas in 2016 for the N rates of 0, 80, and 240 kg ha -1 .…”
Section: Experiments With Genotypes and Nitrogen Ratessupporting
confidence: 90%
“…An increase in corn grain yield resulting from different doses of nitrogen has been observed (Peruzzo et al, 2015;Portugal et al, 2017;Scotta et al, 2018;Moreira et al, 2019). Many studies demonstrated a linear relationship between grain yield and N doses.…”
Section: Introductionmentioning
confidence: 99%
“…Neto et al (2012), em experimento com milho pipoca e feijão consorciados, evidenciou que o milho não apresenta oscilações na produção e parâmetros de rendimento de grãos, havendo a manutenção da produção do cultivo solteiro. Scotta et al (2018), que consorciaram milho com brachiária (Brachiaria decumbens) ou feijão guandu (Cajanus cajan), observaram que nenhuma das variáveis nas espigas de milho foram afetadas com o plantio consorciado das culturas.…”
Section: Discussionunclassified
“…Londrina, v. 44, n. 4, p. 1523-1540, jul./ago. 2023 of nodes during early growth stages (Ecco et al, 2020). However, the timing of LHM application, which often precedes wheat sowing, may restrict N availability to plants during crucial phases of crop development (Pegoraro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%